Assessment of Patient Skin Dose During Routine X-ray Procedures in Selected Libyan Healthcare Facilities - Abtisam A . Alakrout; Retaj F. Kamouka; Aisha M. Shamaka (African Journal of Advanced Pure and Applied Sciences, 2025)
Background: Medical use of X-rays is one of the largest sources of human radiation exposure today, with an equivalent dose of 3 mSv, compared to 2.4 mSv from natural background radiation. The risk of cancer induction exists within these dose levels, necessitating the avoidance of excessive radiation exposure and the use of doses higher than required for specific examinations. Therefore, estimating the Entrance Surface Dose (ESD) for patients undergoing X-ray examinations is crucial for radiation protection. Materials and Methods: This study aimed to assess patients’ skin exposure to radiation during routine radiographic examinations for five selected procedures in four healthcare facilities in Libya. The examinations included chest (PA, LAT), lumbar spine (AP, LAT), foot (AP, LAT), hand (AP, LAT), and knee (AP, PA, LAT). The study involved 169 patients, with a mean age of 42 ± 15 years, a mean weight of 74 ± 12 kg, and a mean height of 1.68 ± 0.08 m. The radiation dose for participants was estimated by determining the X-ray tube output (kVp) and imaging factors, such as patient weight, height, exposure time, and tube current. Results: The mean ESD (mGy) for each examination was as follows: Chest: 1.58 ± 0.30, Lumbar spine: 13.8 ± 7.5, Foot: 1.65 ± 0.28, Hand: 1.58 ± 0.19, Knee: 3.58 ± 0.59. Conclusion: The study concluded that patient exposure to radiation during routine radiographic examinations is inevitable. Therefore, it is essential to regularly review patient doses to achieve the ALARA (As Low as Reasonably Achievable) principle, ensuring that doses remain as low as possible without compromising diagnostic quality. This study provided essential baseline information on patient radiation dose levels in the assessed healthcare facilities. A significant variation in dose values for the same examination was observed, attributed to differences in examination techniques, radiographers’ proficiency, and patient weight. The study also emphasizes the importance of radiation protection programs in diagnostic radiology, effective quality control, and establishing reference dose levels in these healthcare facilities.